2024
DOI: 10.5534/wjmh.220262
|View full text |Cite
|
Sign up to set email alerts
|

Differential Proteomic Analysis of Human Sperm: A Systematic Review to Identify Candidate Targets to Monitor Sperm Quality

Abstract: Purpose The advent of proteomics provides new opportunities to investigate the molecular mechanisms underlying male infertility. The selection of relevant targets based on a single analysis is not always feasible, due to the growing number of proteomic studies with conflicting results. Thus, this study aimed to systematically review investigations comparing the sperm proteome of normozoospermic and infertile men to define a panel of proteins with the potential to be used to evaluate sperm quality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…It has been suggested that the expression of genes encoding proteins related to fertilization may serve as markers for predicting male fertility [33]. Table 1 lists some testis-specific proteins that are considered candidates towards a marker panel for male fertility impairment [34,35]. Among the proteins secreted in the male reproductive system, we identified acrosin (P10323, ACR), which is important in the merger between sperm and egg.…”
Section: Testis-specific Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the expression of genes encoding proteins related to fertilization may serve as markers for predicting male fertility [33]. Table 1 lists some testis-specific proteins that are considered candidates towards a marker panel for male fertility impairment [34,35]. Among the proteins secreted in the male reproductive system, we identified acrosin (P10323, ACR), which is important in the merger between sperm and egg.…”
Section: Testis-specific Proteinsmentioning
confidence: 99%
“…Total acrosin activity may be considered a sensitive biochemical marker for the clinical evaluation of unexplained infertility in males [36]. In addition to ACR, the zona pellucida binding protein (Q9BS86, ZPBP) and A-kinase anchor protein 4 (Q5JQC9, AKAP4) were also highlighted due to their role in male reproductive tissues, association with infertility phenotypes, and participation in specific biological functions in spermatozoa [35]. AKAP4 plays a crucial role in maintaining the integrity of sperm fibrous sheaths and normal sperm motility.…”
Section: Testis-specific Proteinsmentioning
confidence: 99%